Landscapes and borders of metropolitan ruralities of Mendoza, Argentina - Pastor, Gabriela Claudia (2020)
This paper is based on the notion of frontier as an analytical category associated with the concepts of rural peri-pherization and urban extractivism. In the metropolitan foothills of Mendoza, Argentina it seeks to identify and understand the socio-territorial transformations, by analyzing the sequence of borders that have characterized the articulations between rural and urban spaces in border areas. This contribution provides a reading of the territorial and landscape transformations from a comprehensive view of rurality. It explains the dynamics of these territories in light of the processes of urban growth.